Effect of Saccharides Coating on Antibacterial Potential and Drug Loading and Releasing Capability of Plasma Treated Polylactic Acid Films - Karakurt, Ilkay; Ozaltin, Kadir; Pištěková, Hana; Vesela, Daniela; Michael-Lindhard, Jonas; Humpolícek, Petr; Mozetič, Miran; Lehocky, Marian (International journal of molecular sciences, 2022)
More than half of the hospital-associated infections worldwide are related to the adhesion of bacteria cells to biomedical devices and implants. To prevent these infections, it is crucial to modify biomaterial surfaces to develop the antibacterial property. In this study, chitosan (CS) and chondroitin sulfate (ChS) were chosen as antibacterial coating materials on polylactic acid (PLA) surfaces. Plasma-treated PLA surfaces were coated with CS either direct coating method or the carbodiimide coupling method. As a next step for the combined saccharide coating, CS grafted samples were immersed in ChS solution, which resulted in the polyelectrolyte complex (PEC) formation. Also in this experiment, to test the drug loading and releasing efficiency of the thin film coatings, CS grafted samples were immersed into lomefloxacin-containing ChS solution. The successful modifications were confirmed by elemental composition analysis (XPS), surface topography images (SEM), and hydrophilicity change (contact angle measurements). The carbodiimide coupling resulted in higher CS grafting on the PLA surface. The coatings with the PEC formation between CS-ChS showed improved activity against the bacteria strains than the separate coatings. Moreover, these interactions increased the lomefloxacin amount adhered to the film coatings and extended the drug release profile. Finally, the zone of inhibition test confirmed that the CS-ChS coating showed a contact killing mechanism while drug-loaded films have a dual killing mechanism, which includes contact, and release killing.
Keywords: biokompatibilní potahované materiály; Staphylococcus aureus; Coated Materials, Biocompatible; Chitosan; karbodiimidy; polyestery; Anti-Bacterial Agents; chitosan; antibakteriální látky; Polyesters; Carbodiimides